Ozone application in fresh fruits and vegetables - Mohd Aziz, Khawarizmi; Ding, Phebe (Universiti Putra Malaysia Press, 2018)
The demand of fruits and vegetables across the world had increased throughout the years which urge the need to have better and proper way to increase produce safety, quality and postharvest life. Traditionally pesticides or other chemicals had been used to encounter microbes related to postharvest diseases. Over time, consumers are concern towards health effect of consuming those produce treated with chemicals. Ozone is one of the approach that provide both of the needs to deal with pathogenic microbes and also give no harmful residue throughout the process. Several reports had proven that ozone can almost kill or inhibit all pathogenic microbes on treated commodity which promote higher quality and postharvest life during storage. This review focus and summarise the use of ozone in the form of aqueous and gaseous towards fresh produces, its benefits and also the precaution during ozone application.